Antagonism of Trichoderma harzianum and Clonostachys rosea against fungi associated with grapevine decline in Kurdistan region - Iraq - Haleem, Raed A.; Saedo, Khadeja A.; Abdullah, Samir K. (Science Journal of University of Zakho, 2016)
This study was carried out to test in vitro the efficiency of Clonostachys rosea and Trichoderma harzianum as bicontrol agents against fungi isolated from declining grapevine trees in Iraq. In vitro assays showed a good antagonistic activity of C. rosea against the colony growth of Phaeoacremonium aleophilum and Cylindrocarpon destructans; the values of x coefficient were 0.90 of each with significance differences comparing with antagonism behavior against B. parva (x=1.43). T.harzianum showed highly response against the growth of all tested fungi with x coefficient ranged between 0.50 - 0.65; which was higher than that of C.rosea. The test revealed significant growth inhibition of C.rosea against P.aleophilum, which were 46.60%, 55.17%, 74.33% in the concentrations 5%, 10%, and 15% respectively. No inhibition appeared in the growth of both Botryosphaeria parva and Macrophomina phaseolina .The filtrate of T. harzianum decreased the growth of P. aleophilum to 19% and 19.83% with the filtrate concentrations 10% and 15% respectively. B.parvawas also affected by the concentration 10% and 15% of T harzianum, the inhibition reached to 12.66% and 12.82% respectively. The inhibition in the growth of M. phaseolina ranged between 20 – 28%, but in the C. destrcuctans have recorded the lowest inhibition percentages in the concentration 5% (5.25%) and 10% (6.91%).